On the monsoons of South America Part 1 : Climatological structure and circulation (MAUSAM, 2004)
Earth-atmosphere radiation budget analyses as well as conventional meteorological analyses are used to establish a case for a well-developed monsoon circulation over South America operating between a heat source over the continent and a heat sink over the surrounding oceans during the southern summer. Evidence is produced to show that the criterion of seasonal reversal is met not only by the wind field but also by the fields of several other variables, such as temperature, isobaric height, specific humidity and rainfall. Computed meridional-vertical circulations for different seasons appear to suggest that the onset and withdrawal of monsoon over the continent are related to the movement of Hadley and Monsoon circulation cells following the seasonal movement of the heat source. A revised definition of the monsoon is proposed in accordance with the findings of the study.